Torn apart and reunited: impact of a heterotroph on the transcriptome of Prochlorococcus - Biller, Steven J (ISME J, 2016)
Microbial interactions, whether direct or indirect, profoundly affect the physiology of individual cells and ultimately have the potential to shape the biogeochemistry of the Earth. For example, the growth of Prochlorococcus, the numerically dominant cyanobacterium in the oceans, can be improved by the activity of co-occurring heterotrophs. This effect has been largely attributed to the role of heterotrophs in detoxifying reactive oxygen species that Prochlorococcus, which lacks catalase, cannot. Here, we explore this phenomenon further by examining how the entire transcriptome of Prochlorococcus NATL2A changes in the presence of a naturally co-occurring heterotroph, Alteromonas macleodii MIT1002, with which it was co-cultured for years, separated and then reunited. Significant changes in the Prochlorococcus transcriptome were evident within 6 h of initiating co-culture, with groups of transcripts changing in different temporal waves. Many transcriptional changes persisted throughout the 48 h experiment, suggesting that the presence of the heterotroph affected a stable shift in Prochlorococcus physiology. These initial transcriptome changes largely corresponded to reduced stress conditions for Prochlorococcus, as inferred from the depletion of transcripts encoding DNA repair enzymes and many members of the ‘high light inducible' family of stress–response proteins. Later, notable changes were seen in transcripts encoding components of the photosynthetic apparatus (particularly, an increase in PSI subunits and chlorophyll synthesis enzymes), ribosomal proteins and biosynthetic enzymes, suggesting that the introduction of the heterotroph may have induced increased production of reduced carbon compounds for export. Changes in secretion-related proteins and transporters also highlight the potential for metabolic exchange between the two strains.